Analisis Penerapan Green Accounting dalam Mendukung Sustainability pada Usaha Mikro, Kecil, dan Menengah (Studi Fenomenologi pada Rumah Produksi Amplang di Kecamatan Benua Kayong, Kabupaten Ketapang) - Suryani, Endang (Jurnal KIAFE, 2024)
This study examines the implementation of green accounting in supporting business sustainability among amplang-producing micro, small, and medium enterprises in Benua Kayong District, Ketapang Regency. The study employs a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, observations, and document analysis involving the business owner, employees, and members of the surrounding community. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that the business owner has limited knowledge of accounting and does not understand green accounting conceptually. The enterprise also does not maintain formal financial records or separately identify environmental costs. However, several operational practices reflect the informal implementation of green accounting, including maintaining production-site cleanliness, reusing production equipment, processing fish skin into salted products, using fish heads for food, and utilizing fish bones and internal organs as animal feed. These practices reduce production waste, support environmental responsibility, and contribute to business continuity. Thus, although green accounting has not been formally recorded or reported, its practical implementation has supported the sustainability of the amplang production business.